Microwave sensing of Andreev bound states in a gate-defined superconducting quantum point contact - Connolly,M (Physical Review Research, 2022)
We use a superconducting microresonator as a cavity to sense absorption of microwaves by asuperconducting quantum point contact defined by surface gates over a proximitized two-dimensionalelectron gas. Renormalization of the cavity frequency with phase difference across the point contact isconsistent with coupling to Andreev bound states. Near π phase difference, we observe randomfluctuations in absorption with gate voltage, related to quantum interference-induced modulations in theelectron transmission. Close to pinch-off, we identify features consistent with the presence of a singleAndreev bound state and describe the Andreev-cavity interaction using a dispersive Jaynes-Cummingsmodel. By fitting the weak Andreev-cavity coupling, we extract ~GHz decoherence consistent with chargenoise and the transmission dispersion associated with a localized state.